Comparison of Copper Level and Color Vision in Pulmonary Tuberculosis Patients Before and After Ethambutol Treatment in Category I and II - Febria Restissa; Ahmad Rasyid; Devi Azri Wahyuni (Sriwijaya Journal of Ophthalmology, 2020)
Introduction: to determine the correlation between duration of ethambutol and copper levels in serum with color vision disorder examined with Farnsworth Munsell 100 Hue (FM100) in patients with tuberculosis. Methods: This study was an explorative observation of 20 samples during November 2017 - January 2018 period. Comparative analysis using independent t-test, paired t-test, Wilcoxon test and Mann-Whitney test, while correlation analysis using Spearman's test and Pearson's test. Results: There was a significant difference of FM100 value before and after in category I (p=0.000) with increase of total error value 11.80+5.31 or category II (p=0.000) with increase of total error value 15.00+7.41. There was significant difference of Cu2+ level before and after in category I (p=0.005) with decrease of Cu2+ level 15.57+5.04 mg/dL or category II (p=0.005) with decrease of Cu2+ level 31.66+7.35 mg/dL. There was significant correlation between color vision and duration of ethambutol (p=0.000), but there was no significant correlation of Cu2+ with color vision (p>0.05). Conclusion: The duration of Ethambutol was related to changes in color vision examined with FM100.